1976
DOI: 10.1007/bf00220127
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy of the glomerular filtration membrane in the rat kidney

Abstract: The rat kidney was perfused with saline and glutaraldehyde, treated with Murakami's tannin-osmium impregnation method, ethanol-freeze cracked and dried by the critical point method. Gold-palladium evaporated specimens were observed in a field-emission scanning electron microscope. The glomerular filtration membrane, fractured in different planes was observed with the following results: 1. Adjacent pedicles originate from different podocytes. No interpedicular bridges of apparent cytoplasmic nature could be fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 14 publications
3
18
0
Order By: Relevance
“…In four of the six adult guinea pigs examined, the following were revealed in the sinusoidal endothelial cell of the liver: 1) the occurrence of lipid droplets and 2) of the tortuous canalicular system in the cytoplasm as well as 3) the so-called "pored domes" (FuJITA et al, 1976;YosHINAUI and FUJITA, 1982). In TEM preparations, lipid droplets are preserved, moderately blackened by osmic acid.…”
Section: Sinusoidal Endothelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In four of the six adult guinea pigs examined, the following were revealed in the sinusoidal endothelial cell of the liver: 1) the occurrence of lipid droplets and 2) of the tortuous canalicular system in the cytoplasm as well as 3) the so-called "pored domes" (FuJITA et al, 1976;YosHINAUI and FUJITA, 1982). In TEM preparations, lipid droplets are preserved, moderately blackened by osmic acid.…”
Section: Sinusoidal Endothelial Cellsmentioning
confidence: 99%
“…By using a scanning electron microscope (SEM), FUJITA et al (1976) revealed, in a fenestrated glomerular endothelial sheet (lamina f enestra or areolae fenestratae) of the rat kidney, domes and shelves formed of a f enestrated cytoplasmic sheet above the ordinary level of the endothelial lining, and proposed a hypothesis that they might be formed by the anastomosis of microvilli and thus be involved in the replacement of depleted parts of the aleolae fenestratae. Thereafter, Y0sHINARI and FUJITA (1982) used SEM to observe the glomerular endothelium in the rabbit kidney, and revealed the domes both on the aleolae fenestratae and on the perikaryonal swelling, designating them as the "pored domes.…”
Section: Kupffer Cellsmentioning
confidence: 99%
“…Previous studies have noted the regional abundance of microvilli on the luminal surface of the endothelium, and the occasional fusing of the top of the microvilli has been described (FUJITA et al, 1976;FUJITA and MIYOSHI, 1985). These findings suggest that active and repeated budding and fusion of the microvilli from the endothelial surface may result in the formation of this structure.…”
Section: Discussionmentioning
confidence: 82%
“…The structure of a typical, single-layered lamina or areola fenestrata of the glomerulus has been fully described by several authors using both transmission and scanning electron microscopy (YAMADA, 1955;FUJITA et al, 1976;FUJITA and MIYOSHI, 1985). The present findings were in good accordance with those already described.…”
Section: Resultsmentioning
confidence: 99%
“…5). The structural meaning of the processes is not known at present, though this type of processes has been previ- ously reported in the glomerular capillaries and regarded as a precursory structure for partial renewal of the sieve plate of the endothelial cytoplasm (WOLFF, 1966;WOLFF and MERKER, 1966;FUJITA et al, 1976;YOSHINARI and FUJITA, 1982).…”
Section: Resultsmentioning
confidence: 99%